Automated decision-making system for management of information protection channels - Herasimov, S.; Shmatko, O. (Національна академія Національної гвардії України, 2024)
Decision-making tasks when managing information security channels are not automated at a sufficient level [1, 2]. This leads to the fact that decisions to block information ransmission channels are made on the basis of subjective assessments of decision makers (DMs), or using insufficiently complete information models. At the same time, in the process of functioning of information transmission channels, the results of the work of bodies identifying and blocking information leakage channels are poorly taken into account
Keywords: information protection channels